TINJAUAN PENERAPAN AKUNTANSI MANFAAT KARYAWAN - Jazid Jazid (EKUITAS (Jurnal Ekonomi dan Keuangan), 2005)
Accountancy of employees benefit arranges confession; measurement and reporting of obligation (or assets) of post employee benefit. Next, burden of employees benefit was  allocated to during year of service employees. To reach best estimate in measurement of employees benefit obligation (at the time of terminating year of service employees) and converting to present value was needed an assumption actuarial. The practice of this accountancy is visible at existence of confession and reporting of obligation (or assets) of employee’s benefit in financial position report, and burden of employee’s benefit in accounting of loss and profit report. The reporting give influence to less to the company performance, because it can decreasing to the ratio of financing structure health and the profit.The practice of accountancy of employee's benefit  for Indonesia have arranged by  SFAS 24 and 57. Although these SFAS have gone into effective of commencing from date of January 1st 1995 and from date of January 1st 2001, but the applying is still less. Condition prerequisite to applying accountancy of benefit employees require confession for obligatory past event and commitment to fulfill the law obligation. The low of enforcement of law in general  including compliance of UU ketenagakerjaan, domination of the practical consideration of business, and complication of the actuarian calculation is cause such weak precondition.The practice of accountancy of employee's benefit for Indonesia is more effctive at the  emiten and or the public company, for the financial statement including cover of period of commencing from January 1st 2000. It is motivated for applying of the good corporate governance and the Kepmennaker 150/2000. This positive growth are more better since of application of UU Ketenagakerjaan 13/2003 and SFAS 24 revised at year 2004 (earlier application are recommended).To evaluate how far the practice of accountancy of employee's benefit is needed an evaluation to the regulation which have relation to developing of precondition above; and also to the accountancy of benefit employees itself.